Characterization and Sensory Aspects of “Peulh Type” Fresh Cheese - Ferial Aziza Benyahia-Krid; Ouarda Aissaoui-Zitoun; Halima Boughellout; Faiza Adoui; Amani Harkati; Cocou Rogatien Bakou; Denis Wodo; Mohammed Nassereddine Zidoune (Current Research in Agricultural and Food Science Vol. 5, 2021)
The calotropine, a vegetable coagulating enzyme, extracted from Calotropis procera is very used in the preparation of traditional Peulh cheese. Peulh cheese has attracted a lot of interest from stakeholders in the West African dairy industry. In this study, the fresh leaves of this vegetable were used to coagulate raw milk for the production of the fresh cheese Peulh type which was characterized by the physicochemical and sensory aspects. The results showed that this traditional cheese presented a total dry extract of 32.49%, pH 6.28, a lactic acidity of 0.14 p.cent, a protein content of 28.30% and a sweet whey with pH 5.90. The Peulh cheese making yield is 55.45% expressed on dry basis. The sensory aspects showed that it has a firm texture, elastic, not sticky, with a lactic odour and a lactic flavour and has an overall persistence in the mouth of about 15 seconds.